2015
DOI: 10.1093/ije/dyv087
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertension and hyperglycaemia with socioeconomic contexts in resource-poor settings: the Bangladesh Demographic and Health Survey

Abstract: Increasing levels of wealth and educational attainment were associated with an increased likelihood of having hypertension and hyperglycaemia in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
41
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 38 publications
16
41
0
7
Order By: Relevance
“…12,23 In contrast to this evidence, our study shows that the prevalence of hypertension was greater among people with higher SES groups, which is consistent with recent studies conducted in LMICs, 2426 particularly in South Asia. 15,27 Substantial differences between male and female were observed in the association between SES and hypertension, which is consistent with previous studies in developed countries. 15,28,29…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…12,23 In contrast to this evidence, our study shows that the prevalence of hypertension was greater among people with higher SES groups, which is consistent with recent studies conducted in LMICs, 2426 particularly in South Asia. 15,27 Substantial differences between male and female were observed in the association between SES and hypertension, which is consistent with previous studies in developed countries. 15,28,29…”
Section: Discussionsupporting
confidence: 91%
“…15,27 Substantial differences between male and female were observed in the association between SES and hypertension, which is consistent with previous studies in developed countries. 15,28,29…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Studies that previously investigated prevalence and risk factors for hypertension in Nepal and other countries have found that these vary according to age, sex, body weight, race/ethnicity, place of residence, marital status, education level, socio‐economic status, and concomitant diseases such as diabetes, dyslipidemia, or stress . Furthermore, due to similar restrictions for assessing prevalence from a nationally representative dataset, studies investigating the determinants of pre‐hypertension or hypertension in Nepal are also limited by a shortage in recently collected data and the availability of only small‐scale studies mainly conducted in a community or a particular region .…”
Section: Introductionmentioning
confidence: 99%